2009
DOI: 10.1128/jcm.01521-08
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Human Immunodeficiency Virus RNA Analysis of Dried Blood Spots for Diagnosis of Infections in Infants

Abstract: The Gen-Probe Aptima human immunodeficiency virus type 1 (HIV-1) RNA assay was adapted for the diagnosis of HIV infection in infants by using dried blood spots. The assay was 99% sensitive (128/129) and 100% specific (162/162). This may prove useful in resource-limited settings, since it precludes the need for a phlebotomist and maintenance of a cold chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Dried fluid spots or solid carriers have already been used for decades in the postnatal screening of certain congenital disorders and diseases. Solid carriers have also been successfully used in studies detecting and genetically characterizing measles virus strains, as well as in studies assessing viral load and genotypic resistance for human immunodeficiency virus (HIV) (2,14,23). As dried material on a solid carrier is neither hazardous nor inflammable, applying genital self-samples on these solid carriers (like FTA cartridges) can solve storage and transportation problems.…”
mentioning
confidence: 99%
“…Dried fluid spots or solid carriers have already been used for decades in the postnatal screening of certain congenital disorders and diseases. Solid carriers have also been successfully used in studies detecting and genetically characterizing measles virus strains, as well as in studies assessing viral load and genotypic resistance for human immunodeficiency virus (HIV) (2,14,23). As dried material on a solid carrier is neither hazardous nor inflammable, applying genital self-samples on these solid carriers (like FTA cartridges) can solve storage and transportation problems.…”
mentioning
confidence: 99%
“…Stevens et al (11) also reported improved specificity when DBS with S/CO ratios less than 10 were repeated. Analytic specificity in HIV-exposed, uninfected children Ͻ18 months of age has been consistently high, ranging from 99.4 to 100% (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Kerr et al (10) found that DBS from 5 of 8 adults with HIV RNAs Ͻ50 cp/ml were detected in the Aptima assay. Similarly, Stevens et al (11) performed dilution experiments with DBS and found that the Aptima assay generated reactive results that were 1 to 3 log units more sensitive than the Roche Amplicor assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer reports detection rates of 98.5% for 30 RNA copies/ml, 82.6% for 10 copies/ml, 42.5% for 3 copies/ml, and 19.4% for 1 copy/ml, and the assay is designed to detect all major groups (e.g., M, N, and O) and subtypes of HIV-1 (9,10). Currently, the Aptima HIV assay is clinically employed in situations in which HIV-1 antibodies may not yet be present, including the diagnosis of acute or primary infection in symptomatic patients (6) and targeted and routine screening for defined patient populations (3,8), and in settings in which the presence of antibodies may not reflect disease status, such as screening of newborns of infected mothers (11,14,16). Potential advantages of using the Aptima HIV assay instead of WB analysis to confirm HIV infection in clinical samples with repeatedly reactive EIA results include (i) less subjective result interpretation since the Aptima HIV assay generates tangible numerical values rather than a series of bands that must be visually compared to controls, (ii) a reduction in the number of indeterminate results since the Aptima HIV assay uses a technology that is distinctly different from the current antibody-based tests used for screening and confirmation, (iii) a decrease in the time to obtain results, and (iv) the comparative ease of simultaneously processing and analyzing large numbers of samples if necessary.…”
mentioning
confidence: 99%